2012
DOI: 10.1002/aur.1220
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of Wh‐Questions Precedes Their Production in Typical Development and Autism Spectrum Disorders

Abstract: Lay Abstract Children with autism produce few wh-questions, compared to their typically developing peers. It is unclear if this is because of social-pragmatic difficulties, or if they have not yet learned the grammar for asking wh-questions. If children do not know how to use grammatical rules to produce questions, they might simply repeat sentences that they have heard without completely understanding them first. We visited the homes of 15 children with autism and 18 typically developing children with similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
4
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 59 publications
10
100
4
6
Order By: Relevance
“…In addition, approximately 30% of children with ASD may not develop meaningful spoken language by school age (Tager-Flusberg & Kasari, 2013); if clinical decisions are based on language production, these children may be exposed to telegraphic input in treatment for an extended period of time. This is concerning because some young children with ASD, like typically developing children, may be capable of understanding more complex aspects of language than they produce (Goodwin, Fein, & Naigles, 2012). Failing to consistently expose children to grammatical features of language presents the real possibility that they will not be learned, which may be particularly harmful for young children who already have trouble learning morphosyntactic features of language (Eigsti et al, 2007;Fey, 2008;McGregor et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, approximately 30% of children with ASD may not develop meaningful spoken language by school age (Tager-Flusberg & Kasari, 2013); if clinical decisions are based on language production, these children may be exposed to telegraphic input in treatment for an extended period of time. This is concerning because some young children with ASD, like typically developing children, may be capable of understanding more complex aspects of language than they produce (Goodwin, Fein, & Naigles, 2012). Failing to consistently expose children to grammatical features of language presents the real possibility that they will not be learned, which may be particularly harmful for young children who already have trouble learning morphosyntactic features of language (Eigsti et al, 2007;Fey, 2008;McGregor et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3,14,21 Developmental differences are seen with the wh-question video, as TD children showed significant comprehension at 28 months of age, whereas significant comprehension was first found in children with ASD at 54 months of age. 10 Therefore, children with ASD are delayed in learning how to correctly interpret questions such as "What did the apple hit?" …”
Section: Representative Resultsmentioning
confidence: 99%
“…Videos can be created to assess a wide range of specific components of linguistic knowledge, such as Subject-Verb-Object word order, wh-questions, and tense/aspect suffixes on verbs; videos can also assess principles of word learning such as a noun bias, a shape bias, and syntactic bootstrapping. 10,14,17,21,24 Videos include characters and speech that are visually and acoustically salient and well tolerated by children with ASD. …”
mentioning
confidence: 99%
“…Similarly, several researchers have found that, when given standard preferential-looking and elicited production tasks, English speaking children with ASD seem to acquire knowledge of SUBJECT VERB OBJECT word order in a similar way to typically-developing children (Naigles et al 2011;Naigles and Tovar 2012;Swensen et al 2007). Finally, Goodwin et al (2012) showed that when assessed on their comprehension of wh-questions (a particularly complex syntactic structure), children with ASD performed similarly to language-matched (though not age-matched) controls.…”
Section: Discussionmentioning
confidence: 97%